EVALUATION COMPREHENSION OF THE CHILDREN AND ADOLESCENT PHYSICAL GROWTH IN THE COURSE OF THE POPULATION RESEARCH - V.R. Kuchma; N.A. Skoblina ("Paediatrician" Publishers LLC, 2008)
The urgency of the given research is intimately related to the necessity to choose the comprehension approaches to the evaluation of the children's physical growth, which may be applied in monitoring of the children collectives health status, planning and performance of the preventive and sanitary events at the group and population levels. The authors studied the socially different children collectives and examined 3,600 children and adolescents. They showed that the use of the regional modified regression scales, complex schemes and centile tables, i.e. regional standards based approaches to the evaluation of the physical growth would be comprehensive for the physical growth features of the children collectives subject to ethnic, climate and geographic as well as social and economic differences.Key words: physical growth, evaluation approaches, children, adolescents.